2002
DOI: 10.1248/bpb.25.1391
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 Genotype-Related Pharmacokinetics and Pharmacodynamics.

Abstract: The multidrug resistant transporter MDR1/P-glycoprotein, the gene product of MDR1, is a glycosylated membrane protein of 170 kDa, belonging to the ATP-binding cassette superfamily of membrane transporters. MDR1 acts as an energy-dependent efflux pump that exports its substrates out of cells. MDR1 was originally isolated from resistant tumor cells as part of the mechanism of multidrug resistance, but over the last decade, it has been elucidated that human MDR1 is also expressed throughout the body to confer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 161 publications
9
111
1
1
Order By: Relevance
“…Hoffmeyer et al and Tanabe et al found that 3435 T/T or 2677 T/T, T/A were associated with lower P-gp expression levels in the intestine 21) and placenta, 17) though the opposite results were reported in MDR1 mRNA expression. 22) Sakaeda et al reported that 3435 T/T coding exon 26 produced higher MDR1 mRNA expression on duodenal specimen 22,23) and peripheral blood mononuclear cells stimulated by lipopolysaccharide. 24) These observations suggest that MDR1 polymorphisms for exon also participate the change in P-gp activity on BBB, though the clinical investigation for verapamil penetration into the brain 25) does not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmeyer et al and Tanabe et al found that 3435 T/T or 2677 T/T, T/A were associated with lower P-gp expression levels in the intestine 21) and placenta, 17) though the opposite results were reported in MDR1 mRNA expression. 22) Sakaeda et al reported that 3435 T/T coding exon 26 produced higher MDR1 mRNA expression on duodenal specimen 22,23) and peripheral blood mononuclear cells stimulated by lipopolysaccharide. 24) These observations suggest that MDR1 polymorphisms for exon also participate the change in P-gp activity on BBB, though the clinical investigation for verapamil penetration into the brain 25) does not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) MDR1 is a glycosylated membrane protein of 170 kDa, belonging to the ATP-binding cassette superfamily, and acts as an energydependent efflux pump that exports substrates out of cells. [9][10][11] Numerous clinical studies have concluded that MDR1 overexpression was associated with a failure of chemotherapy; however, there is no information on the relationship between the effects of oxidative stress on cell proliferation or death and MDR1 expression levels.…”
mentioning
confidence: 99%
“…Approximately 25 SNPs for the mdr1 gene were identified (13)(14)(15). However, the most important SNPs in Caucasians are G2677T/A and C3435T as these SNPs have been shown to be involved in P-glycoprotein expression and phenotype (13,16).…”
Section: Gstm1-t1 Polymorphisms and Platinum/paclitaxelmentioning
confidence: 99%